2016
DOI: 10.48550/arxiv.1601.03883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How to retrieve additional information from the multiplicity distributions

Grzegorz Wilk,
Zbigniew Włodarczyk

Abstract: Multiplicity distributions P (N ) measured in multiparticle production processes are most frequently described by the Negative Binomial Distribution (NBD). However, with increasing collision energy some systematic discrepancies have become more and more apparent. They are usually attributed to the possible multi-source structure of the production process and described using a multi-NBD form of the multiplicity distribution. We investigate the possibility of keeping a single NBD but with its parameters dependin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 46 publications
(74 reference statements)
1
7
0
Order By: Relevance
“…One can see that only our MNBD fit reproduces the experimentally obtained coefficients C j . In [3] it is also shown that the amplitude of these oscillations decrease with the narrowing of the pseudo-rapidity window, |η|, in which the data are collected (eventually they vanish for small |η|) and that the same behavior is also observed for the ALICE data [6] (albeit with stronger oscillations in this case). A word of caution is in order at this point.…”
Section: Another Look At Multiplicity Distributions P(n)mentioning
confidence: 56%
See 4 more Smart Citations
“…One can see that only our MNBD fit reproduces the experimentally obtained coefficients C j . In [3] it is also shown that the amplitude of these oscillations decrease with the narrowing of the pseudo-rapidity window, |η|, in which the data are collected (eventually they vanish for small |η|) and that the same behavior is also observed for the ALICE data [6] (albeit with stronger oscillations in this case). A word of caution is in order at this point.…”
Section: Another Look At Multiplicity Distributions P(n)mentioning
confidence: 56%
“…Both m(N) and the probability of particle emission p(N) are now non-monotonic functions of N (p(N) = const in the standard NBD). This non-monoticity is located in the region of small multiplicities N [3]. Note that such a spout-like form of the proposed modification is just one of the simplest possible choices of parametrization bringing agreement with data.…”
Section: How To Fit Presently Available Datamentioning
confidence: 62%
See 3 more Smart Citations